Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I'm trying to solve

$$\int_{-\infty}^{\infty}{\frac{1}{(4+x^2)\sqrt{4+x^2}} \space dx}$$

By substituting $x=2\tan{t}$. I get as far as:

$$\int_{x \space = -\infty}^{x \space = \infty}{\frac{1}{(4+(\underbrace{2\tan{t}}_{x})^2)\sqrt{4+(\underbrace{2\tan{t}}_{x})^2}} \cdot \underbrace{2(1+\tan^2t) \space dt}_{dx}} = \dots$$

$$\dots = \frac{1}{4} \cdot \int_{t \space = -\infty}^{t \space = \infty}{\frac{1}{\sqrt{1+\tan^2t}} \space dt}$$

Now what? Have I done anything wrong? I don't see how I could continue from now on.

share|cite|improve this question
$1+\tan^2x=\sec^2x$ (follows from $\sin^2x+\cos^2x=1$) – yoyo Dec 20 '11 at 20:32
Your steps are correct, except for a small thing: when you do a substitution (here, for $x$ in terms of $t$), you should remember to calculate the limits for $t$ and plug that in the new integral. In this example, the limits for $t$ are $-\frac{\pi}{2}$ and $\frac{\pi}{2}$; do you see why? // To proceed, one could use the identity: $1 + \tan^2 x = \sec^2 x = \frac{1}{\cos^2 x}$. – Srivatsan Dec 20 '11 at 20:33
I'm not good at limits so I left those values the same until I'm done with the substitution. We haven't learned anything called $sec(x)$ at uni, I should probably look it up. – Dimme Dec 20 '11 at 20:36
Do look it up! Without it you could note that $1+\tan^2 x=1+\frac{\sin^2 x}{\cos^2 x}=\frac{\sin^2 x+\cos^2 x}{\cos^2 x}=\frac{1}{\cos^2 x}$. – André Nicolas Dec 20 '11 at 20:43
"Solve" is the wrong word. You don't solve an integral; you evaluate an integral. – Michael Hardy Dec 20 '11 at 21:41
up vote 7 down vote accepted

Your substitution is the way to go in this problem. To complete the substitution however, I recommend that you calculate the new limits for $t$. An alternate approach is to postpone this till the end, but this approach invariably ends up confusing if there's a string of substitutions. In this example, as $x \to -\infty$, $t = \arctan x \to -\frac{\pi}{2}$; similarly as $x \to \infty$, we have $t \to \frac{\pi}{2}$. Therefore, after substitution, the integral becomes $$ \int_{-\frac{\pi}{2}}^{\frac{\pi}{2}} \frac{1}{\sqrt{1+\tan^2 t}} \, dt. $$

To proceed further, you need to use the following cousin of the Pythagorean theorem: $$ 1 + \tan^2 t = \sec^2 t . $$ This identity is extremely important and useful in practice -- not the least in manipulating integrals like this. One should be reminded of this identity whenever one comes across an expression like $\sqrt{1 + \tan^2 t}$ or $\sqrt{1+ x^2}$. By the way, the proof of this identity is based on the standard Pythagorean theorem: $$ 1+ \tan^2 t = 1 + \frac{\sin^2 t}{\cos^2 t} = \frac{\cos^2 t + \sin^2 t}{\cos^2 t} = \frac{1}{\cos^2 t} = \sec^2 t. $$ From this, it follows that $$ \frac{1}{\sqrt{1 + \tan^2 t}} = |\cos t|. $$

Thus the integral becomes $$ \int_{-\frac{\pi}{2}}^{\frac{\pi}{2}} |\cos t| \, dt. $$ Can you take it from here?

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.